Sternal elevation by the crane technique during pectus excavatum repair: A quantitative analysisCentral MessagePerspective - Erik R. de Loos, MD; Jean H.T. Daemen, MD; Nadine A. Coorens, MSc; Jos G. Maessen, MD, PhD; Yvonne L.J. Vissers, MD, PhD; Karel W.E. Hulsewé, MD, PhD (JTCVS Techniques)
Introduction: The crane technique is used to facilitate sternal elevation to provide safe mediastinal passage during the Nuss procedure. The aim was to objectively quantitate the elevation of the crane by 3-dimensional chest images acquired during the Nuss procedure. Methods: A prospective cohort study was conducted. Patients undergoing the Nuss procedure were eligible. Sternal elevation was achieved by the crane technique providing a simultaneous lift of the anterior chest wall and reduction of the pectus excavatum depth. Both effects were evaluated. Three-dimensional surface images were acquired before incision, following sternal lift, and after bar implantation and quantitatively compared. Reduction of the external pectus excavatum depth was expressed as a percentage. Results: Thirty patients were included. Ninety percent were male, with a median age of 15.5 years (interquartile range [IQR], 14.5-17.4), Haller index of 3.56 (IQR, 3.09-4.65), and external pectus depth of 18 mm (IQR, 11-23). Sternal elevation by the crane provided a median 78% (IQR, 63-100) reduction of the deformity, corresponding with a residual depth of 3 mm (IQR, 0-7). The percentual reduction diminished with increasing depth of the sternal depression (correlation, –0.86). Besides reducing the deformity, the crane caused an elevation of the anterior chest over a large surface area with a maximum lift of 26 mm (IQR, 19-32). Conclusions: The crane is an effective sternal elevation technique, providing 78% reduction of the sternal depression, although its effect lessens with increasing depth. In addition, it produces an elevation of the anterior chest over a large surface area.